If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X/6+11=X
We move all terms to the left:
X/6+11-(X)=0
We add all the numbers together, and all the variables
-1X+X/6+11=0
We multiply all the terms by the denominator
-1X*6+X+11*6=0
We add all the numbers together, and all the variables
X-1X*6+66=0
Wy multiply elements
X-6X+66=0
We add all the numbers together, and all the variables
-5X+66=0
We move all terms containing X to the left, all other terms to the right
-5X=-66
X=-66/-5
X=13+1/5
| 72=4x+16 | | 14x-26+5x=180 | | -31/2x-4=-381/8 | | 1/5x3=10 | | x+-34.9=-0.6 | | 5(3n+5)=7(9n+3)+5 | | 0.5(7x+14)=1.3-(x-2) | | -y-2y-3=15y-10 | | 2x−73=−1 | | 2-3x=-x8 | | 4n+24=10 | | 21.3+x=-40.7 | | 1/2t^2-162=0 | | 7(8+y)=2y+6 | | T=7n+5 | | 9x+12=7x+6 | | x+1=7+2 | | 5x5=-3(-x-1) | | 127÷y=540-73 | | x+-52.3=-34.6 | | 23.1+x=-23.8 | | x/3/5=5/6 | | x+-20.9=-7.3 | | 9x-6=2x=4 | | 2x+25=-6x-4 | | 120t-40-80t=-40 | | 93=180-z180- | | 3x^2+7=3x+7 | | 5(2-6x)=2(10x-20) | | 15x-40=65 | | -12x+27=-3x-40 | | 3(2x+5)=2(8+4x) |